1998
DOI: 10.1111/j.1469-7793.1998.803bg.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of voltage‐activated [Ca2+]i transients in single smooth muscle cells isolated from pregnant rat uterus

Abstract: The intracellular calcium concentration ([Ca2+]i) was measured at 35 °C using the fluorescent indicator indo‐1 in patch‐clamped, single uterine myocytes from pregnant rats to investigate the relationship between depolarization, Ca2+ current (ICa) and [Ca2+]i. Membrane depolarization activated ICa and produced a [Ca2+]i transient. The rapid increase in [Ca2+]i occurred at the same time as the inward ICa. Both ICa and the increase in [Ca2+]i were abolished by nifedipine (10 μm). When the membrane potential was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 28 publications
4
117
0
Order By: Relevance
“…The results are consistent with a previous study that mibefradil inhibited the frequency as well as amplitude of uterine contractility (Asokan et al, 2002 ]i and force. According to the previous report, high K + -induced contraction is due to Ca 2+ influx through L-type Ca 2+ channel by membrane depolarization (Shmigol et al, 1998;Coleman et al, 2000). In the present study, we also showed that 1 μM nifedipine, L-type Ca 2+ channel blocker, completely inhibited high K + -induced contraction.…”
Section: Discussionsupporting
confidence: 69%
“…The results are consistent with a previous study that mibefradil inhibited the frequency as well as amplitude of uterine contractility (Asokan et al, 2002 ]i and force. According to the previous report, high K + -induced contraction is due to Ca 2+ influx through L-type Ca 2+ channel by membrane depolarization (Shmigol et al, 1998;Coleman et al, 2000). In the present study, we also showed that 1 μM nifedipine, L-type Ca 2+ channel blocker, completely inhibited high K + -induced contraction.…”
Section: Discussionsupporting
confidence: 69%
“…Electrical stimulation of these SMCs, in which close proximity of VGCCs and RyRs within the caveolar domains was confirmed with 3D-immunofluorescence and electron microscopy (Moore et al, 2004), triggers an abrupt RyR-mediated Ca 2+ release at multiple sub-PM regions ('hot spots ', Ohi et al, 2001;Morimura et al, 2006). The ability of Ca 2+ entering the SMC via VGCCs to induce RyR-mediated Ca 2+ release has also been demonstrated in voltage-clamp experiments performed on SMCs from pregnant myometrium (Shmigol et al, 1998), ileum (Kohda et al, 1997), mesenteric artery (Bolton and Gordienko, 1998), cerebral arteries (Kamishima and McCarron, 1997) and portal vein (Coussin et al, 2000). However, other research groups working on different or even the same SMC type failed to detect any evidence of CICR (Fleischmann et al, 1996;Kamishima and McCarron, 1996;Bradley et al, 2002).…”
Section: Introductionmentioning
confidence: 88%
“…Although activation of the SR Ca 2+ release by Ca 2+ entering the cell via VGCCs has been demonstrated in voltage-clamp experiments performed on different types of visceral and vascular SMCs (Kamishima and McCarron, 1997;Kohda et al, 1997;Bolton and Gordienko, 1998;Shmigol et al, 1998;Coussin et al, 2000), there is a number of studies (e.g. Bradley et al, 2002;2004) (Bradley et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of isolated myocytes using voltage pulses revealed the current-voltage relationships of the pregnant myometrial SMCs in rats (18,34) and in humans (7,37). Application of single voltage pulses demonstrated that the Ca 2ϩ current (I Ca ) through L-type VOCCs significantly increased C Ca,i , whereas repetitive stimulation with pulse trains revealed that both VOCC opening and Ca 2ϩ -induced Ca 2ϩ release (CICR) from the sarcoplasmic reticulum (SR) are responsible for the increased C Ca,i (18). The entry current following depolarization of rat myometrial cells comprises two components, which were identified based on differences in their activation and inactivation properties as well as in their kinetics.…”
mentioning
confidence: 99%